2021
DOI: 10.1186/s12876-021-01755-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of endoscopic retrograde cholangiopancreatography for acute cholangitis associated with distal malignant biliary obstruction

Abstract: Background There is a lack of studies regarding the optimal timing for endoscopic retrograde cholangiopancreatography (ERCP) in patients with cholangitis caused by distal malignant biliary obstruction (MBO). This study aims to investigate the optimal timing of ERCP in patients with acute cholangitis associated with distal MBO with a naïve papilla. Methods A total of 421 patients with acute cholangitis, associated with distal MBO, were enrolled for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the literature, few studies reported only MBO-associated AC[ 17 ], some gave an account of only CBDS-associated AC[ 11 , 18 ], and most reported mixed results for AC of different etiologies[ 3 , 13 - 15 ]. Although the etiology of AC varies, studies explicitly comparing the clinical presentations and outcomes of AC of distinct etiologies are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, few studies reported only MBO-associated AC[ 17 ], some gave an account of only CBDS-associated AC[ 11 , 18 ], and most reported mixed results for AC of different etiologies[ 3 , 13 - 15 ]. Although the etiology of AC varies, studies explicitly comparing the clinical presentations and outcomes of AC of distinct etiologies are rare.…”
Section: Discussionmentioning
confidence: 99%
“…In the overall population analysis, we found that MBO-associated AC had significantly higher 30-d mortality than CBDS-associated AC, which is consistent with previous studies[ 3 , 4 ]. Regardless of the etiology, time to ERCP has been reported to be a prognostic factor associated with 30-d mortality in AC patients[ 13 , 16 , 17 ]. In a study of distal MBO-associated AC, Park et al [ 17 ] reported that urgent ERCP (within 24 h of ED arrival) improved 30-d mortality in moderate-to-severe AC patients.…”
Section: Discussionmentioning
confidence: 99%
“…As to when is the optimal timing for ERCP for acute cholangitis, this is an important clinical issue. The results of the comparative studies regarding the timing of ERCP are summarized in Table 1 6–14 . The recommended optimal timing of drainage depends on the severity of cholangitis based on the severity grading criteria 15 .…”
Section: Ercp For Acute Cholangitismentioning
confidence: 99%
“…However, 30-d mortality in AC has been reported to range from 1% to 16% between studies, which may be one of the reasons leading to inconsistent conclusions about the optimal timing of ERCP[ 11 , 13 - 15 ]. Differences in mortality may be due to different patient populations in different studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tan et al [ 11 ] included 43% of MBO patients in their study and reported a 30-d mortality rate of 16%. However, Park et al [ 15 ] included only patients with AC associated with distal MBO and reported an overall 30-d mortality rate of 4.8%. Therefore, there may be some other factors associated with 30-d mortality between studies.…”
Section: Discussionmentioning
confidence: 99%